PELATIHAN PENINGKATAN KUALITAS PADA LAPORAN KEUANGAN BUMDES DENGAN MEMANFAATKAN APLIKASI DIGITAL â€œBUKU WARUNGâ€ DI DESA TANAH MERAH KECAMATAN GALANG KABUPATEN DELI SERDANG - Yolla Sarah Ananda Harahap; Sri Fitria Jayusman; Indah Ayu Lestari (Cattleya Darmaya Fortuna, 2022)
The specific goals and targets of this community service activity are intended for Village-OwnedEnterprises (BUMDES) located in Tanah Merah Village, Galang District, DeliSerdang Regency. beable to manage finances well so that reports will be made properly as well.This activity was carriedout for 3 months, as for training in the preparation of financial reports by utilizing a specialapplication on financial reports to assist partners in solving problems. The methods used in thisactivity are as follows: (1) collecting problems faced by partners through FGD (Focus GroupDiscussion), (2) analyzing partner needs to find the best solution to the situation at hand, (3)conducting training to solve problems that arise. faced, (4) make activity reports as a form ofaccountability